IMPLEMENTASI NILAI KARAKTER PADA MAHASISWA JURUSAN MPI FAKULTAS TARBIYAH DAN KEGURUAN IAIN IMAM BONJOL PADANG - Jum Anidar (Jurnal Al-Taujih : Bingkai Bimbingan dan Konseling Islami, 2015)
Character is the values of human behavior associated with the Almighty God, ourselves, our fellow human beings, the environment, and nationality embodied in thoughts, attitudes, feelings, words, and actions based on religious norms, laws, manners, culture and customs. In this study, which will be disclosed are: 1) Application of character values of respect and courtesy MPI student of Faculty of education and teacher IAIN Imam Bonjol Padang.2) Application of character values of responsibility majors MPI Faculty of education and Teaching IAIN Imam Bonjol Padang. This research field research (field research) that is descriptive kualalitatif. The technique of collecting data through observation and interview techniques.